Analysis of High School Students' Pocket Money Use in Smoking Behavior - Muhammad Iqbal; Lusiandro Julian Petrix; Syarifah Ema Rahmaniah; Herlan Herlan; Annisa Rizqa Alamri; Meisya Dwi Lianti; Dede Oktavianus (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Indonesia is part of the world's largest cigarette production. Smoking behavior has become a common addictive behavior in Indonesia. For most teenagers, smoking behavior has become a common thing, but parents consider it as something that has a negative connotation. Smoking is an activity that is currently much loved by Indonesian teenagers. Attempts at restrictions related to smoking behavior are very difficult. Many negative effects can be caused by smoking. Cigarettes when consumed can be a source of various health problems such as cancer, heart, and respiratory disorders, as well as other things that are certainly a health hazard for the smoker. The existence of these conditions, of course, endangers the younger generation, and there must be Prevention of smoking activities carried out by young children. This study used literature study research methods. This study uses data collection techniques using secondary data. This study involved cigarette users consisting of high school children. The results of this study showed that high school children in Singkawang City, West Kalimantan use their money to buy cigarettes. Some of those who filled out the survey data knew about cigarettes through the intermediary of friends. The problem of smoking in today's era is that of course it will indirectly harm many people who are around smokers because the user is exposed to cigarette smoke.